2017
DOI: 10.1111/joim.12596
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in HIV infection and pathogenesis

Abstract: The aim of autophagy is to re‐establish homeostasis in response to a variety of stress conditions. By forming double‐membrane vesicles, autophagy engulfs damaged or superfluous cytoplasmic material and recycles degradation products for new synthesis or energy production. Of note, the same mechanism is used to capture pathogens and has important implications in both innate and adaptive immunity. To establish a chronic infection, pathogens have therefore evolved multiple mechanisms to evade autophagy‐mediated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 96 publications
(140 reference statements)
0
64
0
Order By: Relevance
“…Some studies have suggested that PZA potentiation by the host may be related to drug upregulation of the autophagy pathway [96] . Multiple studies have reported the occurrence of dysregulated autophagy during diseases that cause altered immune states [97][98][99][100] While many outstanding questions remain, these studies indicate that the appropriate cell-mediated responses are critical for optimal PZA efficacy, and both local and systemic immune modulation are highly impactful for PZA efficacy.…”
Section: Pza and The Host Environmentmentioning
confidence: 99%
“…Some studies have suggested that PZA potentiation by the host may be related to drug upregulation of the autophagy pathway [96] . Multiple studies have reported the occurrence of dysregulated autophagy during diseases that cause altered immune states [97][98][99][100] While many outstanding questions remain, these studies indicate that the appropriate cell-mediated responses are critical for optimal PZA efficacy, and both local and systemic immune modulation are highly impactful for PZA efficacy.…”
Section: Pza and The Host Environmentmentioning
confidence: 99%
“…The aim of autophagy is to reestablish homeostasis in response to a variety of stress conditions. HIV infection represents one of the best-characterized systems in which autophagy is disarmed by a virus using multiple strategies to prevent the sequestration and degradation of its proteins and to establish chronic infection [324]. HIV infection has been shown to induce and inhibit autophagy.…”
Section: Hiv and Autophagymentioning
confidence: 99%
“…Tat inhibits autophagy in neurons and also inhibits autophagosome/lysosome fusion by interaction with LAMP2A; this might be the reason that neurons will proceed to apoptosis because of inhibition of autophagy in HIV-associated neurodegenerative disease (HAND). Tat induces autophagy by interaction with BAG3 in glial cells [324]. Nef, an HIV-1 accessory protein, interacts with IRGM and then IRGM is capable of activating autophagy by favoring the assembly of a ULK1/BECLIN-1/ATG16 complex.…”
Section: Hiv and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…In two review articles, various aspects of the relationship between cell death mechanisms and HIV are discussed. Thus, Nardacci et al present evidence for role of autophagy in HIV infection and pathogenesis [3]. HIV infection represents a system in which a virus via several strategies deactivates the autophagy.…”
mentioning
confidence: 99%